Restorative Justice in Criminal Acts of Corruption - Vega pratama (Universitas Muhammadiyah Surakarta, 2021)
This article intends to elaborate the model of corruption crimes resolved in a system of restorative justice that occurs in the State of Indonesia. This article emphasizes that efforts to eradicate corruption are not merely to provide punishment for those who are proven with the most severe punishment, but so that all countries that are caused by acts of corruption prevention can be returned in a short time. Technically, this study finds that there are 3 (three) conditions that cause the loss of the unlawful nature of a criminal act of corruption, namely: the suspect or defendant is disadvantaged; the state is not disadvantaged; community served. Based on the three conditions illustrate if the criminal act of corruption has returned the entire proceeds of the criminal act of corruption along with all the profits obtained from the results of the criminal act of corruption by the criminal act of corruption then basically the perpetrator is disadvantaged, the country does not suffer financial losses and the public can be served through returning all proceeds of corruption and all the benefits thereof. As a consequence, in order to create a restoring judicial process, this article desires to reduce the socio-economic burden of the state and law enforcement energy in handling cases of corruption.